An extra priming dose of hepatitis A vaccine to adult patients with rheumatoid arthritis and drug induced immunosuppression – A prospective, open-label, multi-center study. Issue 21 (January 2018) - Rosdahl, Anja; Herzog, Christian; Frösner, Gert; Norén, Torbjörn; Rombo, Lars; Askling, Helena H.
Abstract: Background: Previous studies have indicated that a pre-travel single dose of hepatitis A vaccine is not sufficient as protection against hepatitis A in immunocompromised travelers. We evaluated if an extra dose of hepatitis A vaccine given shortly prior to traveling ensures seroconversion. Method: Patients with rheumatoid arthritis (n = 69, median age = 55 years) treated with Tumor Necrosis Factor inhibitor(TNFi) and/or Methotrexate (MTX) were immunized with two doses of hepatitis A vaccine, either as double dose or four weeks apart, followed by a booster dose at six months. Furthermore, 48 healthy individuals, median age = 60 years were immunized with two doses, six months apart. Anti-hepatitis A antibodies were measured at 0, 1, 2, 6, 7 and 12 months. Results: Two months after the initial vaccination, 84% of the RA patients had protective antibodies, compared to 85% of the healthy individuals. There was no significant difference between the two vaccine schedules. At twelve months, 99% of RA patients and 100% of healthy individuals had seroprotective antibodies. Conclusion: An extra priming dos of hepatitis A vaccine prior to traveling offered an acceptable protection in individuals treated with TNFi and/or MTX. This constitutes an attractive pre-travel solution to this vulnerable group of patients.